MEMBANGUN IDENTITAS NASIONAL MELALUI TEKS: REVIEW SINGKAT TERHADAP TEKS SASTRA DALAM BUKU TEKS BAHASA INDONESIA - Sarasati, Ruruh (Diksi, 2021)
(Title: Building National Identity through Text: A Brief Review of Literary Texts in Indonesian Language Textbooks). Indonesia is a multi-ethnic, multi-culture, and multi-religion country. Nowadays, Indonesia is facing some sirous problem related with nationality, therefore, cultivating students national identity is important because students are generation who will run this country. Students must be aware of their identity in respect of country, ethnicity, and culture, one of its way is through literary text. This article reviews literary text that found in student textbook and how it can construct and cultivate national identitiy. There are four kinds of national identity in peotry written on the textbook: religion, language, etnic, and local custom.Keywords: national identity, literary text, text book, students